Characterization and kinetic study of a nanostructured rhodium electrode for the hydrogen oxidation reaction - Montero, María de Los Angeles (2013)
The hydrogen oxidation reaction was studied on a nanostructured rhodium electrode at different rotation rates. The electrode was prepared via sputtering on a glassy carbon disc support and it was characterized by X-ray Photoelectron Spectroscopy (XPS), Atomic Force Microscopy (AFM) and cyclic voltammetry, which allowed verifying the nanostructured morphology and the absence of any phase other than metallic rhodium. The real surface area was evaluated by CO stripping voltammetry. Experimental current density (j) – overpotential (η) curves of the hydrogen oxidation reaction were obtained in the range −0.015 V ≤ η ≤ 0.25 V at different rotation rates in sulphuric acid solution. They were correlated by kinetic expressions derived from the Tafel–Heyrovsky–Volmer mechanism and thus the kinetic parameters were evaluated. It was verified that over this overpotential region the reaction proceeds through the simultaneous occurrence of the Tafel–Volmer and the Heyrovsky–Volmer route.